Asymmetric 1, 2‐Carbamoyl Rearrangement of Lithiated Chiral Oxazolidine Carbamates and Diastereoselective Synthesis of α‐Hydroxy Amides. Issue 43 (14th June 2022) - Ghosh, Arun K.; Basu, Amartyo J.; Hsu, Che‐Sheng; Yadav, Monika
Abstract: Asymmetric 1, 2‐carbamoyl rearrangement of lithiated 2‐alkenyl carbamates has been investigated. Deprotonation of chiral 2‐alkenyl oxazolidine carbamates with sec ‐butyllithium in ether at −78 °C followed by warming of the resulting 1‐lithio‐2‐alkenyl derivatives to room temperature resulted in 1, 2‐carbamoyl rearrangement to provide α‐hydroxy amides. The rearrangement proceeded with excellent diastereoselectivity and in good to excellent isolated yield of the α‐hydroxy amide derivatives. The substrate scope of the reaction was investigated with a variety of 2‐alkenyl and benzyl oxazolidine carbamates. A stereochemical model is provided to explain the stereochemical outcome associated with the rearrangement. Acid‐catalyzed removal of the chiral oxazolidine afforded α‐hydroxy acid in high optical purity. Abstract : Asymmetric 1, 2‐carbamoyl rearrangement of chiral 2‐alkenyl oxazolidine carbamates were investigated. These rearrangements provided α‐hydroxy amide derivatives with excellent diastereoselectivity and in good to excellent isolated yields. The substrate scope of the reaction was examined with a variety of 2‐alkenyl and benzyl oxazolidine carbamates. The observed high degree of diastereoselectivity was rationalized using a stereochemical model.